Instruments’ validation of access to motivation, skills, and use of digital technology: EFL context in Indonesia - Lantip Diat Prasojo; Wiwik Wijayanti; Lia Yuliana; Nurtanio Agus; Akhmad Habibi; Mohd Faiz Mohd Yaakob (Universitas Syiah Kuala, 2020)
The purpose of this study was to validate instruments regarding digital technology access among Indonesian English as a Foreign Language (EFL) faculty members during the Corona Virus Disease 2019 (COVID-19). An EFL Faculty member’s Access to Digital Technology (EFL-FADT) scale was adopted from previous relevant studies consisting of Motivation, Skills, and Use. A total of 235 EFL faculty members from three public and three private universities in Indonesia participated in this study, selected through cluster random sampling. A survey design was applied to examine the factor structure of the EFL-FADT. The survey data were computed through the steps of Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) with IBM SPSS 23 and SPSS AMOS 23. Through the EFA with Varimax rotation, two factors emerged from Motivation, three from Skills, and two from Use. The result successfully mapped the proposed model. The CFA approach verified the instrument which was satisfactory for Indonesian EFL faculty members. The findings informed 25 valid and reliable indicators. The measured scale achieves psychometric properties. It can provide future studies with a tool to capture EFL faculties’ access to digital technology.